The effect of green envelope components on green building value. Issue 2 (18th April 2017) - Ab. Azis, Shazmin Shareena; Sipan, Ibrahim; Sapri, Maimunah; Abdul Jalil, Rohaya; Mohammad, Izran Sarrazin
Abstract : Purpose: The purpose of this paper is to identify green envelope building components of residential buildings applicable under hot and humid climates and to analyze the effect of these components on building value. Design/methodology/approach: The authors place an emphasis on green envelope components that influence building value and which are derived based on their integration into a building envelope structure that is applicable under hot and humid climates. This is performed through identification of green benefits of each green envelope component based on literature reviews and in relation to green criteria listed by the Malaysia Green Building Index (GBI). Consequently, a quantitative analysis has been conducted to determine the effect of these green envelope components on building value by means of a questionnaire distribution among 550 property valuation practitioners in Malaysia. However, in order to certify respondents' credibility, the authors analyzed questionnaires answered by property valuation practitioners with experience in green valuation. Findings: The findings show that there are ten green envelope components currently certified under GBI Malaysia and applicable for hot and humid climates. There are three green envelope components that can increase property values, specifically: solar photovoltaic, green living wall and green roof. However, eight of the green envelope components have no effect on building value. Research limitations/implications: Due to the relative immaturity of the green building market in Malaysia, the authors were unable to analyze the actual percentage of increment on building value as conveyed by each green envelope component. Originality/value: This paper aims to provide understanding of the effect of individual green envelope components on building value rather than merely the value of green buildings in general. It proves that green building envelope components do in fact contribute to an increase in green building values. As the green building market in Malaysia is still in its infancy, this study is significant in that it prepares the Malaysian green building market to attain a new level by providing valuation practitioners with awareness of green building values and new knowledge concerning the effect of individual green components on building values. Hence, it is anticipated that this study can assist property valuation practitioners in conducting valuations of green buildings in the future.